(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Health care facilities are an essential aspect of our society, with the goal of reducing healthissues and eliminating urgent threats to people’s health. As a result, it is the responsibility of hospitalsand healthcare facilities to protect public health. This might be done directly via patient treatment orindirectly by creating a clean, healthy environment for their staff and the community. Patil andcolleagues Waste is created throughout the healthcare delivery process, which includes sharps, humantissues or body parts, and other infectious items. The basic idea for a sustainable approach toBiomedical Waste (BMW) Management is guided by examining the amount and pattern of bio-medicalwaste formation, its segregation, classification, and treatment of corresponding category waste. Thecurrent state of effluent treatment and waste management need triangulation strategies, including wastereduction, hazardous impact prevention, and economically feasible pollution control technology